Rapid Profiling Cell Cycle by Flow Cytometry Using Concurrent Staining of DNA and Mitotic Markers - Shen, Yuqing (Bio Protoc, 2017)
The flow cytometric quantitation of DNA content by DNA-binding fluorochrome, propidium iodide (PI) is the most widely used method for cell cycle analysis. However, the commonly used methods are time-consuming and labor-intensive and are incompatible with staining of mitotic markers by fluorescent-labeled antibodies. Here, we report an optimized simple protocol for rapid and simultaneous analysis of characteristic mitotic phosphorylated proteins and DNA content, permitting the quantification of cells in mitosis, G(1), S and G(2) stage in a single assay. The protocol detailed here employs detergent-based hypotonic solution to rapidly permeabilize cells and allows simultaneous staining of DNA with PI and mitotic marker, phospho-Histone H3, with specific antibody within 20 min. The protocol requires only inexpensive and commercial available reagents and also enables a rapid and complete analysis of cell cycle profile.